“Biar Mirip K-pop Idol”: Optimalisasi Penampilan K-pop Dance Cover di Kota Makassar - Saraswati, Andi Irma (Emik, 2023)
Cosmetic products are important in changing the appearance of the face to look like a K-pop idol. The ideal facial appearance standard that the dance cover wants to achieve is one that reflects glowing, thin cheeks, long and colored hair, and a no makeup, makeup look. Although the existing literature has examined how to look as similar as possible to a dance cover, a few if any, has looked at their references in the selection and use of cosmetic products, and this article fills this gap. Using qualitative approach, this study involves ten informants, consisting of four men and six women. Their age ranges between 19 and 27 years, and they are active members of AEON dance cover who also work in different sectors (freelancers, bank employees/frontliners, models. Data collection was conducted by combining observation and interviews. The study shows that face is the part of individual body for dance cover where make-up is most optimized because face is the most important part of being able to determine how similar the dance covers is to the K-pop idol being played. Cosmetic products play a significant role in optimizing the appearance of dance covers to as much as similar to their K-pop idols. Therefore, to optimize the most similar and the best facial appearance, the totality of dance cover is very important. This totality is not only related to the use of make-up cosmetic products (that are visible on the surface), but also related to the use of facecare cosmetic products behind the make-up). both before and after performing. While cosmetics makeup consists of facial, eye and lip makeup; cosmetic care consists of daily care and plus-plus treatment. However, whatever product is used really depends on skin type and the suitability of the product for individual's face. When the product used is suitable (cocok) for the skin in question, then the use of product will be continued. However, when the product is not suitable, then trying (coba) another product is an alternative, until the dance cover finds a product that suits their facial skin. Coba (trying) and cocok (suitable) are conceptually the basis for getting products that suits individual skin. Although information about cosmetic products is obtained by dance covers from social medias (TikTok, Instagram, YouTube, in selecting products, they rely more on YouTube as a valid source of information than other social medias. This is because reviews on YouTube are reviewed by the users themselves, while reviews on other social media (such as TikTok and Instagram) are created by content creators and are intended to promote the products being reviewed